Scoping Review: Why is Public Health Integrated into Medical Education? - Duarsa, Artha Budi Susila; Anulus, Ayu; Zoraya, Sabrina Intan (Indonesian Journal of Medicine, 2024)
Background: Medical students who get community-involved medical education will be better equipped to address the health needs of their communities by integrating public health services into their practice. The importance of public health disciplines for physicians needs to be reinforced in the medical curriculum. Many studies, findings, and discussions report on the importance of this integration. This study aims to identify, decipher, and map the available scientific evidence regarding the importance of public health integration in medical education. Subjects and Method: This was a scoping review study using PUBMED, ProQuest, SCOPUS, Google Scholar, and other related sources. The keywords used in article searches are as follows: "public health" AND "medical education" OR "support" OR "against" OR "proportion" OR "role". From the database used, 1,775 articles were obtained and those who met the criteria were 45 articles. Results: The results were presented in three sub-discussions, namely role, perception, and form of integration. 1) Role: doctors are able to facilitate individual health and address public health problems through health promotion, health policy, evidence-based medicine practices, improving the quality of health data and health services; 2) Perception: Both positive and negative perceptions were reported in these integration-related findings; and 3) Form of integration: public health collaboration in medical education is carried out at the academic and professional stages of doctors. Conclusion: The importance of integrating public health principles into medical education is to encourage the formation of doctors who act as doctors in the curative department as well as public health experts who understand community problems and can address them holistically and comprehensively. Keywords: perception, role, integration, public health, medical education, scooping review